Abrupt chlorophyll shift driven by phosphorus threshold in a small subtropical estuary - Fung, Mai S.; Phipps, Scott W.; Lehrter, John C. (Frontiers in Marine Science, 2022)
Chlorophyll trends in subtropical and tropical estuaries are under characterized and may reveal patterns not shared by their temperate analogues. Detection of trends requires long-term monitoring programs, but these are uncommon. In this study, we utilized an 18-year chlorophyll-a time series from 2002 to 2020 in Weeks Bay, AL, to detect and quantify trends in chlorophyll variability over multiple time scales. Our analysis included up to 30 years of contemporaneous data for variables such as river discharge, nitrogen, and phosphorus to relate the chlorophyll-a trends to environmental drivers. We detected an abrupt shift in chlorophyll-a that was linked to changes in phosphorus and hydrology. The shift followed an abrupt increase in total phosphorus concentration from upstream of the primary river system that discharges into Weeks Bay. Total phosphorus continued to rise after the abrupt shift, but there was no detectable change in chlorophyll-a. We propose that the exceedance of a total phosphorus threshold at 0.1 mg l-1, combined with a period of very low river discharge variability, induced the shift in chlorophyll-a. This shift opposed the pattern of proportional change usually observed as a result of nutrient enrichment. Not all monitoring stations underwent the abrupt shift, which demonstrated the complexity of phytoplankton response to environmental drivers and the significance of spatial differences even over small estuaries.